2005
DOI: 10.1021/es051451s
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dissolved Carboxylates and Carbonates on the Adsorption Properties of Thiuram Disulfate Pesticides

Abstract: The adsorption of thiram and disulfiram onto alpha-Al2O3 and montmorillonite clay has been studied in the presence of small carboxylate anions, bicarbonate, formate, and oxalate. At natural concentrations, HCO3- enhances dramatically the adsorption of both pesticides on alpha-Al2O3 and clay. An analogous significant enhancement of pesticide adsorption is also observed in the presence of formate and oxalate. Density functional theory calculations demonstrate that in solution a stable molecular complex between o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(54 citation statements)
references
References 29 publications
1
51
0
2
Order By: Relevance
“…The surface charge of montmorillonite suspensions were evaluated by two methods: potentiometric acid -base titrations (Schulthess and Sparks, 1986;Stathi et al, 2006;Giannakopoulos et al, 2006) and mass titration (Giannakopoulos et al, 2006;Bourikas et al, 2003).…”
Section: Surface Charge Properties Of Montmorillonitementioning
confidence: 99%
“…The surface charge of montmorillonite suspensions were evaluated by two methods: potentiometric acid -base titrations (Schulthess and Sparks, 1986;Stathi et al, 2006;Giannakopoulos et al, 2006) and mass titration (Giannakopoulos et al, 2006;Bourikas et al, 2003).…”
Section: Surface Charge Properties Of Montmorillonitementioning
confidence: 99%
“…During the HFSLM extraction of target weak organic acids, the dissolved carbon dioxide and carbonate that are widely present in environmental waters are co-extracted by partitioning in the form of CO 2 or H 2 CO 3 into the liquid membrane and then trapping into the acceptor as carbonate. 12 Given the high concentration of dissolved carbon dioxide and carbonate (at mM level) 13 in comparison to the target analytes (at nM level), the trapping of dissolved carbon dioxide and carbonate in the basic acceptor might signicantly reduce the acceptor pH and therefore the extraction efficiency of the target analytes. As the dissolved carbon dioxide and carbonate in reagent water used to prepare standard solutions are negligible, the reduced extraction efficiency of target analytes resulted from the relatively high contents of dissolved carbon dioxide and carbonate in real environmental samples, giving rise to low recovery of analytes.…”
Section: -6mentioning
confidence: 99%
“…In real soils, more than one mechanism may operate simultaneously. So far, several works have attempted to study and/or correlate the role of sorption in connection with the persistence of selected pesticides on soil (Sheng et al, 2001, Stathi et al, 2006. Sheng et al (2001) have reported an unusual nonlinear adsorption isotherm for Ethyl-Parathion on soil organic matter.…”
Section: Introductionmentioning
confidence: 99%
“…This isotherm non-linearity has been attributed, although not proven, to the presence of high surface area carbonaceous material and/or to specific interactions between pesticide and adsorbent (Sheng et al, 2001). Recently we have demonstrated that adsorption of two common dithiocarbamate pesticides, i.e., Thiram and Disulfiram, on soil components such as a-Al 2 O 3 or montmorillonite (Stathi et al, 2006) and humic acids (Stathi et al, 2007) is determined by carbonates at natural concentrations. Natural concentrations of HCO 3 − have been shown to either enhance drastically adsorption of the neutral dithiocarbamates on a-Al 2 O 3 and montmorillonite (Stathi et al, 2006) or to cause severe inhibition of their sorption on humic acid (Stathi et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation